Maintaining sustainable use of the Indonesian telecommunications provider - Sujono, Rusny Istiqomah; Wibowo, Ardy; Maula, Defia Ifsantin; Khodijah, Amalia Siti; Allia, Nik Nor; Trisnawati, Qori Dewi; Sari, Rita Puspita (Jurnal Studi Komunikasi, 2024)
This research investigates customer behaviour in the Indonesian telecommunications sector using Structural Equation Modelling with Partial Least Squares (SEM-PLS) analysis. Surveying 101 respondents, the study explores the relationships between service quality, service attributes, pricing, satisfaction, and customer intentions to reuse telecom products. Key insights include the significant influence of competitive pricing (price value) on customer retention (continuance to use). Interestingly, customer satisfaction doesn’t directly impact the continuance of use, suggesting other factors like network quality might be more pivotal. However, customer satisfaction enhances price value, emphasising its role in perceived service value. Additionally, service quality is a significant determinant of customer satisfaction, and service attributes play a crucial role in shaping perceived value and satisfaction levels. Overall, this research offers valuable insights and strategic recommendations for telecom companies in the Indonesian market, emphasising pricing, service quality, and network attributes as key drivers of customer behaviour.